O-prenylchalcones inhibit cell proliferation and activate apoptosis by inducing mitochondrial dysfunction in gastric cancer cells - José C. Espinoza-Hicks; Yarely M. Salinas-Vera; Javier Camarillo-Cisneros; Alejandro A. Camacho-Dávila; Jessica L. Hernández-Rivera; Nadia Flores-Huerta; Eloisa Ibarra-Sierra; Carlos Pérez-Plasencia; María Elizbeth Álvarez-Sánchez; Ángeles C. Tecalco-Cruz; César López-Camarillo (Discover Oncology)
Abstract Purpose Treatments for gastric cancer are based on neoadjuvant chemoradiotherapy and molecular-targeted therapies, but these modalities lead to poor outcomes. Therefore, identifying and testing novel drugs with potential anticancer properties is highly important. Chalcones are favoured molecules from the perspective of chemical medicine, as they exhibit efficient antitumour effects in various human diseases. In the present study, we investigated the anticancer effects of 11 novel synthetic O-prenylchalcones on AGS gastric cancer cells. Materials and methods O-Prenylchalcones were synthesized via Claisen–Schmidt condensation, and spectroscopic methods were used to confirm their chemical structures. The viability and proliferation of AGS gastric cancer cells treated with 11 different O-prenylchalcones were quantified via MTT assays. Apoptosis was assessed using a Dead Cell Apoptosis Kit and staining with annexin V-FITC/propidium iodide (PI) followed by fluorescence-activated cell sorting (FACS). The activities of caspase-3 and caspase-7 were quantified using the ApoTox-Glo™ Triplex assay. Reactive oxygen species (ROS) levels in AGS cells were examined using the CellROX Green Flow Cytometry Assay Kit. The interactions between the O-prenylchalcones and selected oncoproteins were predicted by first identifying the most stable conformers, and approximately 5,000 structures were evaluated by force field molecular dynamics. The proteins were configured as rigid receptors, whereas the O-prenylchalcones were configured as flexible ligands in a box with dimensions of 100 × 100 × 100 Å. Results AGS gastric cancer cell viability was significantly reduced in a dose-dependent manner after incubation with most of the O-prenylchalcones. In addition, compounds 6e, 7a, 7d, 7e, 7f, 7j, and 7k significantly inhibited cancer cell proliferation. Moreover, treatment with O-prenylchalcones 7a, 7e, and 7j increased AGS cell death due to a profound loss of mitochondrial membrane potential and the activation of apoptosis. Furthermore, cell death upon treatment was accompanied by increased activity of caspase-3 and caspase-7. Additionally, O-prenylchalcone intervention significantly increased the intracellular ROS concentration. Finally, molecular docking was applied to predict the specific binding between compounds 7a, 7e, and 7j and target oncoproteins, including MMP11, MMP7, INHBA, CDC6, and HOXA1. Conclusions Here, we report preliminary data suggesting that O-prenylchalcones inhibit cell proliferation and promote cell death by inducing mitochondrial dysfunction, caspase-3 and caspase-7 activation, and ROS generation in AGS gastric cancer cells. These findings highlight the potential anticancer effects of these compounds, which deserve further study in preclinical murine models to advance their therapeutic applications in gastric cancer. Graphical abstract